Zakat Dalam Telaah QS. At-Taubah: 103: (Penafsiran Enam Kitab) - Sri Riwayati (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
Zakat includes the third pillar of Islam. Zakat is a maliyah ijtima’iyah worship that must be carried out by every muslim. Zakat is one way to cleanse and purify property. The person who has the right to receive zakat is called mustahiq. In social life there is a reciprocal relationship between recipients of zakat and the providers of zakat which can be applied through prayer which has been explained in at-Taubah: 103. In understanding the verse can use one method that is literature review. Literature study is a method of gathering information from various types of media. In the interpretation of at-Taubah: 103 uses various interpretations according to the interpretation of Al-Maraghi, Muyassar, Al-Mishbah, Al-Lubab, Nurul Qur’an andAs-Syafi’i. from the various interpretations of the at-Taubah: 103 it discusses the command to take part of the assets to be forgiven, because it can purify property from the rights of others, as a means to purify oneself and foster a sense of sharing, and prioritize praying between the giver and recipient.